Quba‟ mosque through the eyes of non-Muslim travellers and explorers - Spahic, Omer (IIUM Press, 2023)
This article is an analysis of the Quba‘ mosque as seen through the lenses of non-Muslim travellers and explorers, with special reference to John Lewis Burckhardt and Richard Francis Burton. The two contrasting personalities with equally contrasting perspectives signify a microcosm of the perennial complexion of the East-West (Orient-Occident) and Islamdom-Christendom relationships. John Lewis Burckhardt‘s views are based on the content of his travelogue that resulted from his secret visit to Madinah and its Quba‘ mosque, which is titled ―Travels in Arabia‖, while the standpoints of Richard Francis Burton are extracted from his own travelogue titled ―Personal Narrative of a Pilgrimage to Al-Madinah and Meccah.‖ These are regularly supplemented, compared and juxtaposed with the contents of other books and travel stories produced by both Muslims and non-Muslims. Inevitably, the primary sources used for writing this article were the classical history works about Madinah and a corpus of travel and exploration literature. The research method adopted is a blend of descriptive and historical interpretation, comparison and analysis